Enhancement of Narrative Writing Based on Local Wisdom - Eli Nurliza; Erfinawati Erfinawati; Nurul Azmi; Nursafiah Nursafiah (International Conference on Multidisciplinary Research, 2022)
The purpose of this research is to improve the creative writing skills of junior high school student level through learning based on local wisdom. The method used in this research is the research and development method. The results showed that students' creative writing abilities increased if using the material and learning process used local wisdom-based learning. Local wisdom-based learning will make it easier for students to receive the knowledge gained through the learning process. Keywords: Narrative Writing, Local Wisdom, Creative Writing